Enhancement of crystallinity and toughness of poly (l‐lactic acid) influenced by Ag nanoparticles processed by twin screw extruder. Issue 7 (6th October 2016) - Bautista‐Del‐Ángel, Jesús E.; Morales‐Cepeda, Ana B.; Lozano‐Ramírez, Tomas; Sanchez, Saúl; Karami, Shahir; Lafleur, Pierre
Abstract : Poly(l ‐lactic acid) nanocomposites based on silver nanoparticles (PLA/AgNP) were prepared by melt blending using a twin screw extruder. Nanocomposites at low concentrations were prepared with 0.1, 0.2, and 0.3 wt% of AgNP to enhance the crystallinity and improve the thermal and mechanical properties of PLA. AgNPs smaller than 100 nm which increased the crystallinity of PLA upon the addition were detected by UV–Vis. Crystallinty index of nanocomposites was estimated reaching a maximum of 0.52, where the AgNPs acted as heterogeneous nucleating agent which is correlated with the Ag content. The α and α′ crystals were observed by temperature modulated differential scanning calorimetry and wide angle X‐ray diffraction, thus lattice spacing of more ordered and distorted crystals were corroborated obtaining a higher fraction of α structures when a high content of nanoparticles was added. Moreover, strain at break and toughness of pure PLA were increased from 4.3% to 16.9% and 2.1 to 7.3 MJ/m 3, respectively, modifying the inherent brittleness of PLA. Finally, with the obtained results a correlation was established where more disordered crystals show less resistance to deformation that lead to an enhancement of elongation at break observed in the nanocomposites. POLYM. COMPOS., 39:2368–2376, 2018. © 2016 Society of Plastics Engineers